"A Jewish Maestra and a Lady too": Reflections on Femininity in the Career of Ethel Stark - Rachwal, Maria N. (Canadian Jewish Studies, 2019)
Ethel Stark (1910-2012) was one of the most important conductors and concert violinists in Canada in the Twentieth century. This article highlights how an Austro-Canadian Jewish woman who lived outside the constraints of conventional domesticity, both navigated through and defied the ideals of the “Cult of True Womanhood” and spearheads a movement of feminism in music. I argue that Stark’s exposure to Jewish cultural traditions of social justice and womanhood in her childhood formed a critical dimension of her feminist activism later in her life, and in particular in the founding of The Montreal Women’s Symphony Orchestra (1940).